2022
DOI: 10.4236/ojst.2022.1210027
|View full text |Cite
|
Sign up to set email alerts
|

Laser and Its Application in Periodontology: A Review of Literature

Abstract: Introduction: The use of lasers is an emerging therapy in periodontology, however, controversies regarding its use. Despite the vast amount of literature that is currently available, debates regarding the use of lasers in periodontal therapy continue. This review aims to summarize and clarify the myths surrounding the use of lasers in periodontal therapy, which may offer new hope for the treatment's future. Methods: A comprehensive computer-based search was done using various databases like PubMed, Medline, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…[ 24 28 ] In a study comparing wound healing after scalpel, electrosurgery and Nd: YAG laser surgery in beagle dogs, it was shown that surgical sites appeared to be clinically healed 14 days postoperatively. [ 24 29 ] However, histologically, the electrosurgery site continued to have a high degree of inflammatory infiltrate. Immediately, postoperatively, the laser can offer protection to the surgical site through a coagulum surface and, as mentioned previously, bacterial reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 28 ] In a study comparing wound healing after scalpel, electrosurgery and Nd: YAG laser surgery in beagle dogs, it was shown that surgical sites appeared to be clinically healed 14 days postoperatively. [ 24 29 ] However, histologically, the electrosurgery site continued to have a high degree of inflammatory infiltrate. Immediately, postoperatively, the laser can offer protection to the surgical site through a coagulum surface and, as mentioned previously, bacterial reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown additional benefits with laser use, such as minimal wound contraction and minimal scarring when compared to scalpel surgery. [ 27 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa tipe laser, yaitu CO2, Nd:YAG, Er:YAG, Er,Cr:YSGG, dan diode, telah banyak digunakan untuk perawatan penyakit periodontal dan manajemen jaringan lunak serta jaringan keras. 9,10 Keuntungan yang dapat diperoleh dari penggunaan laser antara lain perdarahan minimal, trauma mekanis minimal, nyeri pascabedah yang lebih rendah, mengurangi formasi jaringan parut, dan mempersingkat waktu bedah. Laser tipe erbium yang digunakan pada ketiga studi inklusi merupakan laser yang digunakan dalam bidang periodontal pada jaringan lunak dan keras.…”
Section: Pendahuluanunclassified
“…Today's laser technologies are utilised in many dental specialties, like periodontology, paediatrics, oral surgery, implantology, and oral pathology [23][24][25].…”
Section: Introductionmentioning
confidence: 99%